Soft Collinear Degeneracies in an Asymptotically Free Theory. (14th February 2012) - Lavelle, Martin; McMullan, David; Steele, Tom
Abstract : In asymptotically free theories with collinear divergences it is sometimes claimed that these divergences are cancelled if one sums over initial and final state degenerate cross-sections and uses an off-shell renormalisation scheme. We show for scalarϕ 3 theory in six dimensions that there are further classes of soft collinear divergences and that they are not cancelled. Furthermore, they yield a nonconvergent series of terms at a fixed order of perturbation theory. Similar effects in gauge theories are also summarised.